Perspectives on the effectiveness of NGO initiatives in Urban agriculture in Zimbabwe - Sammie, Batanai; Nyamutowa, Charles; Gwazane, Munyaradzi (2016)
NGO programmes in developing countries quickly fail after being transferred to beneficiaries. This study used FGDs and case studies to identify some perceived causes of failure of NGO urban agriculture initiatives in Zimbabwe. The study identified the principal-agent relationship between NNGOs and LNGOs as the epicenter of all initiative failures. The study thus recommends that LNGOs negotiate for greater discretion in implementing programmes as well as forge symbiotic long-term relationships with relevant government departments.